Strengthening Educational And Cultural Values Through The International Community Service Program In Pattani, Thailand - Nisa, Mia Kairun; Hudi, Ilham; Attalla, M. Sulthan Raihan; Wahyudi, M. Reno; Bilal, Muhammad; Munawarah, Lathifa; Audi M, Neysa; Rahmadini, Ineke; Adha, Khusnul; Pele, Imanullah Ulu; Arafat, Ismail (International Journal of Research in Community Services, 2024)
The International Community Service Program (KKN) at Kalamullah Al-Qur'an and Multilingual School in Pattani, Thailand, aims to strengthen educational and cultural values through a series of work programs that focus on various aspects of learning and culture. The work programs include: (1) Teaching Program, which improves the quality of education at the elementary, middle, and high school levels with interactive teaching methods; (2) Dream Tree Program, which inspires students to set their dreams and plan for their future; (3) Finger Painting Program, which encourages students' creativity through painting; (4) Direction Sign Program, which facilitates navigation and language comprehension in the school environment; (5) Batik Program, which introduces the art of Indonesian batik as part of cultural heritage; and (6) Introducing Indonesian Cuisine Program, which introduces Indonesian cuisine such as rendang, chicken curry, and chili paste to staff, teachers, and students. These programs not only enrich student’s educational and cultural experiences, but also strengthen the relationship between Indonesia and Thailand. These activities successfully facilitated positive cultural exchanges and deepened the understanding of Indonesian culture and education in Thailand.